The lived experience of stress among fifteen-year-old adolescents: A qualitative study - Rahayu, Reghina Yulia; Darni, Darni; Iskandar, Ayuk Cucuk (Palembang MediRose Publisher, 2025)
Background: Adolescence is a critical developmental stage marked by heightened vulnerability to stress across academic, family, and social domains. Fifteen-year-old students often face multiple pressures that influence their emotional well-being and coping capacity. Understanding how adolescents perceive and respond to stress is essential for designing effective support strategies. Objective: To explore the sources of stress, coping responses, and support needs among 15-year-old adolescents. Methods: A qualitative descriptive study was conducted in Tarakan City, Indonesia. Twenty junior high school students aged 15 years were recruited using purposive sampling. Data were collected through semi-structured face-to-face interviews lasting 40–60 minutes, supplemented by field notes, and analyzed using Miles and Huberman’s interactive model of data reduction, display, and conclusion drawing. Data saturation was reached at 20 participants. Results: Four themes emerged: (1) Complex origins of stress—academic demands, family conflict, and peer challenges created multifaceted stress experiences; (2) Stress responses to challenges—stress manifested in anxiety, sadness, disappointment, lethargy, and somatic complaints; (3) Adaptive and maladaptive coping strategies —adolescents used both constructive approaches (e.g., socializing, drawing, listening to music, exercising) and detrimental behaviors (e.g., self-harm, aggression, smoking, yelling); and (4) Adolescents’ wishes during difficult times—participants expressed a strong desire for parental attention, empathy, and supportive peer relationships. Conclusion: Fifteen-year-old adolescents experience stress from interconnected academic, familial, and social sources that shape diverse emotional and behavioral responses. Their coping strategies range from adaptive to maladaptive, and they consistently seek greater support and understanding from parents and peers. These findings highlight the need for comprehensive, adolescent-centered support systems involving families, schools, and healthcare providers to strengthen resilience and promote mental well-being.